Recent Findings Related to Cardiomyopathy and Genetics - Takanobu Yamada (MDPI AG, 2021)
With the development and advancement of next-generation sequencing (NGS), genetic analysis is becoming more accessible. High-throughput genetic studies using NGS have contributed to unraveling the association between cardiomyopathy and genetic background, as is the case with many other diseases. Rare variants have been shown to play major roles in the pathogenesis of cardiomyopathy, which was empirically recognized as a monogenic disease, and it has been elucidated that the clinical course of cardiomyopathy varies depending on the causative genes. These findings were not limited to dilated and hypertrophic cardiomyopathy; similar trends were reported one after another for peripartum cardiomyopathy (PPCM), cancer therapy-related cardiac dysfunction (CTRCD), and alcoholic cardiomyopathy (ACM). In addition, as the association between clinical phenotypes and the causative genes becomes clearer, progress is being made in elucidating the mechanisms and developing novel therapeutic agents. Recently, it has been suggested that not only rare variants but also common variants contribute to the development of cardiomyopathy. Cardiomyopathy and genetics are approaching a new era, which is summarized here in this overview.